Distribution and invasive potential of the black-tufted marmoset Callithrix penicillata in the Brazilian territory - do Vale, Caroline Almeida; Menini Neto, Luiz; Prezoto, Fábio (Scientia Plena, 2020)
Biological invasions are one of the greatest existing threats to biodiversity. Invasive species can cause economic and environmental damage. Callithrix penicillata is naturally found in the Brazilian savanna and Caatinga. Its introduced populations have become a conservation problem due to its high occupancy potential, native fauna predation, competition with native primates, congeners and hybridization. We used Species Distribution Modeling (SDM) through the Maxent software in this study in order to identify areas with a higher probability of C. penicillata occurrence. The AUC value was close to 1 (AUC=0.966), with a curve value close to 1. Through the Jackknife test we observed that temperature seasonality was the variable most related to distribution (AUC=0.86), which agrees with other studies that show climatic variables influencing primate distribution. The Atlantic Forest in the Southeast and South regions of Brazil was indicated as susceptible to invasion by C. penicillata. The marmoset C. penicillata has become a successful invader of Atlantic Forest areas, causing depreciation in many native species and other problems. However, biological invasions might be mitigated or even extinguished through successful interventions and management.